2020
DOI: 10.21203/rs.3.rs-105938/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toxicity and Risk of Plant-Produced Alkaloids to Daphnia magna.

Abstract: Background Many plants contain phytotoxic alkaloids to deter herbivorous pests and grazing animals. Alkaloids include quinolizidine and indole alkaloids found in the lupin (Lupinus spp.), an ornamental flower and emerging protein crop, as well as pyrrolizidine alkaloids in the ragwort (Senecio jacobaea), an invasive, weed-like flower. When lupins and ragworts are present in large densities in fields, there is a concern that alkaloids may leach into freshwater environments in amounts that may affect non-target … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This is supported by the results of our mesocosm study, where we could show that after precipitation the population density of A. obliquus and D. magna were reduced. A recent study showing that during rainfall the concentration of secondary plant metabolites was about ten times higher in surface water of streams further support our findings (Griffiths et al, 2021; Günthardt et al, 2020; Kisielius et al, 2020). Unfortunately, we could not reliably measure the concentration of 2‐MNQ in the mesocosms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is supported by the results of our mesocosm study, where we could show that after precipitation the population density of A. obliquus and D. magna were reduced. A recent study showing that during rainfall the concentration of secondary plant metabolites was about ten times higher in surface water of streams further support our findings (Griffiths et al, 2021; Günthardt et al, 2020; Kisielius et al, 2020). Unfortunately, we could not reliably measure the concentration of 2‐MNQ in the mesocosms.…”
Section: Discussionsupporting
confidence: 91%
“…If donor plants grow in riparian areas, allelochemicals may cross ecosystem boundaries (Jackrel & Wootton, 2015) and leach into the adjacent water bodies, especially during precipitation, which was shown for allelochemicals from bracken (Skrbic et al, 2021). Ecotoxicological studies in the laboratory, performed with the extracted allelochemical juglone and other natural toxins, revealed negative effects of these compounds on water dwelling organisms, such as an increased mortality in zoo‐ and phytoplankton (Griffiths et al, 2021; Westfall et al, 1961; Wright et al, 2007). Based on these findings, invasive terrestrial plants, that form monospecific stands in riparian areas may not only affect terrestrial native plant species they may additionally affect the neighboring aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When allelochemical producing plants grow in low densities, the amount of allelochemicals leaching into adjacent waters may be negligible. However, it was shown for example that phytotoxins, such as pyrrolizidine alkaloids (PA), produced by Senecio jacobaea or Petasites hybridus, were found in concentrations up to 90 ng/l in small streams and up to 230 ng/l in seepage water from groundwater wells 28,30 . Furthermore, rainfall increased PA concentrations by a factor of ten in stream water, which might be critical for aquatic ecosystems during rainy season 28 .…”
mentioning
confidence: 99%
“…1-4-naphthoquionones, to which 2-MNQ belongs, are a class of redox-active molecules that may cause oxidative stress in cells and have been shown to increase the mortality in parasites (Trypanosoma brucei), human cancer cells, or aquatic invertebrates (Eurytemora affinis) [37][38][39] . In sub-lethal concentrations such compounds can affect the fitness of organisms either by reducing growth, reducing fecundity or compromising the immune system 30,40 . It was shown that a similar compound, juglone (5-hydroxy-1,4-naphthoquinone), an allelochemical produced by the black walnut tree, Juglans nigra, can increase the mortality in D. magna, when the animals are treated with finely ground walnut hulls or the purified substance 37,41 .…”
mentioning
confidence: 99%